A Modified QuEChERS Extraction and LC-MS/MS Method for the Determination of Pesticide Residues in Curry Leaves (Murraya koenigii) - Arimboor, Ranjith; Menon, Karunkara R.; Babu, Natarajan Ramesh; Chandran, Haneesh (Current Chromatography, 2019)
Background: Increased consumer demand for curry leaves free from pesticides demands fast and reliable analytical methods for the analysis of pesticide residues. Objective: The optimization of a QuEChERS based sample preparation technique with improved analytical accuracy by removing interfering matrix components for LC-MS/MS analysis of pesticide residues from curry leaves. Methods: A modified QuEChERS solid phase extraction method was developed and validated for the analysis of 26 pesticides in fresh and dried curry leaves. The effects of the sample preparation steps and column retention time on the matrix suppression of analyte ions were also evaluated. Results: Validation parameters were found within an acceptable range. The matrix effect evaluation studies showed that the QuEChERS sample preparation was able to minimize the ion suppression of analytes due to co-eluting matrix of components and that a d-SPE clean up step had major role in reducing matrix effect. The gradient mobile phase with longer retention time for analytes resulted in comparatively lesser matrix effects than the isocratic mobile phase of non-polar nature. Even after the clean up, a considerable number of compounds had more than 20% reduction in their MS response in the gradient mobile phase. Conclusion: This study emphasized the need of proper sample clean up before a LC-MS/MS analysis and the usage of matrix matched standards and mobile phase that ultimately results in an appropriate analyte separation in reasonable retention times.
Keywords: Murraya koenigii